PRINSIP NON-INTERVENSI PADA MEKANISME ASEAN TERHADAP PENYELESAIAN PELANGGARAN HAK ASASI MANUSIA DI MYANMAR PASCA KUDETA 2021: The Principle of Non-Interference in the ASEAN Mechanism for Resolving Human Rights Violations in Post-Coup Myanmar 2021 - Fernando Raihan Alrafif Muntaco; Aji Wibowo (Faculty of Law, Universitas Trisakti, 2025)
The principle of non-intervention is one of the fundamental norms in the ASEAN organisation that upholds the sovereignty of its member states. This can be seen from various ASEAN legal frameworks that explicitly state the principle. However, this principle poses a dilemma for ASEAN when faced with human rights violations by its member states, such as what happened in Myanmar after the 2021 coup. The formulation of the problem to be researched is whether the implementation of the principle of non-intervention affects ASEAN's mechanism in responding to human rights violations in Myanmar after the 2021 coup? The results of this study show that the principle limits the capacity of ASEAN mechanisms in responding to human rights violations that occurred in Myanmar after the 2021 coup, such as the ASEAN Human Rights Commission (AICHR) and also the Five-Point Consensus (5PC). As a result, the response of ASEAN mechanisms tends to be slow, non-binding, and less independent towards human rights protection.